Lipids - Di Paolo, Gilbert; Wenk, Markus R. (Methods in cell biology, 2012)
Lipids are a broad group of naturally occurring molecules which includes fats, waxes, sterols, fat-soluble vitamins (such as vitamins A, D, E and K), monoglycerides, diglycerides, phospholipids, and others. The main biological functions of lipids include energy storage, as structural components of cell membranes, and as important signaling molecules. This volume of Methods in Cell Biology covers such areas as Membrane structure and dynamics, Imaging, and Lipid Protein Interactions. It will be an essential tool for researchers and students alike.--Provided by publisher.